Contribution of Effective Notetaking in Learning Undergraduate-Level Introductory Physics Courses - Adhikari, Chandra M. (Journal of Nepal Physical Society, 2025)
Taking notes during lectures is one of the required skills, among many others, that students need (i) to master the topic covered in the lecture, (ii) to actively engage in the learning process with minimal to no distractions, (iii) to retain learned knowledge and skills for a longer time, and (iv) in securing higher letter grades. To learn the role of notetaking in learning undergraduate-level introductory physics courses, we present a comparative study of students’ achievement in a mid-terminal exam at a historically black Fayetteville State University (FSU) (i) when students were taught effective notetaking strategies, motivated them to prepare notes and let them use their self-prepared notes in a terminal exam versus (ii) no notetaking scheme was implemented, keeping all other conditions the same. The no-notetaking scheme was used in 4 different sections over a few semesters, and the notetaking scheme was used at the same level of an introductory physics course in 3 different sections in other semesters. Students’ scores in one of the mid-term exams are taken as measurement tools. Grade analysis indicates that effective notetaking enhances students’ letter grades and lowers failure rates.